516 Patient Opinion on The Disruption Caused to Daily Life by Attending A Virtual Clinic Over A Face-to-Face Clinic Appointment in General Surgery During The COVID-19 Pandemic. A Retrospective Patient Feedback Study. (4th May 2021) - Fanning, S; Sturrock, B; Palmer, H; Hussain, A; Carney, C; Jaunoo, S
Abstract: Introduction: During the COVID-19 pandemic many hospitals adopted the use of virtual clinics to reduce in-person contact. We identified the need to assess patient's opinion of the disruption caused to their lives by attending a virtual clinic appointment compared to a face-to-face appointment at a General Surgery department of a UK hospital. Method: 627 patients attended a virtual clinic in General Surgery between 25 th March 2020 and 30 th April 2020. Patients were selected using a random number generator; they were called and asked to complete a google survey which was sent via email. A shorter survey was also conducted over the phone for patients who did not have an email address. Results: 73 patients completed the online or telephone survey. 77.8% (n = 42) reported that they had no problems accessing the virtual clinic. 74.1% of patients (n = 40) agreed that virtual clinics caused less disruption to their daily life. 87.7% (n = 64) saved time by attending the virtual clinic. 67.1% (n = 49) saved two or more hours. 65.8% made a financial saving. Conclusions: Patients found the clinic easy to access. Overall, the virtual clinics cause less disruption to patients' lives than a face-to-face clinic appointment with notifiable savings in both time and money.